Large thermoelectric power factors and impact of texturing on the thermal conductivity in polycrystalline SnSe. Issue 8 (4th February 2016) - Popuri, S. R.; Pollet, M.; Decourt, R.; Morrison, F. D.; Bennett, N. S.; Bos, J. W. G.
Abstract : Large thermoelectric power factors and low thermal conductivities linked to changes in texturing have been observed in consolidated polycrystalline SnSe ingots. Abstract : Single crystals of SnSe have been reported to have very high thermoelectric efficiencies with a maximum figure merit zT = 2.5. This outstanding performance is due to ultralow thermal conductivities. We report on the synthesis of highly textured polycrystalline SnSe ingots with large single-crystal magnitude power factors, S 2 / ρ = 0.2–0.4 mW m −1 K −2 between 300–600 K, increasing to 0.9 mW m −1 K −2 at 800 K, and bulk thermal conductivity values κ 300K = 1.5 W m −1 K −1 . However, small SnSe ingots, which were measured in their entirety, were found to have a substantially reduced κ 300K = 0.6 W m −1 K −1 . Microscopy and diffraction revealed two distinct types of texturing within the hot-pressed ingots. In the interior, large coherent domains of SnSe platelets with a ∼45° orientation with respect to the pressing direction are found, while the platelets are preferentially oriented at 90° to the pressing direction at the top and bottom of the ingots. Fitting the κ ( T ) data suggests an increase in defect scattering for the smaller ingots, which is in keeping with the presence of regions of structural disorder due to the change in texturing. Combining the measured S 2 / ρ with the bulk ingot κ values yields zT = 1.1 at 873 K.